Paula Bunyan - Root, Phyllis (Farrar, Straus and Giroux, 2009)
Recounts the exploits of Paul Bunyan's "little" sister, Paula, who lived in the North Woods, sang three-part harmony with the wolves, and used an angry bear for a foot warmer.